(untitled) (Research, Society and Development, 2022)
Vitamin D plays an important role in the immune system, it is involved in various functions of the human system. That said, the objective is to compare the impacts of the COVID-19 pandemic under the vitamin D levels of lac PUC Goiás patients. It is an observational, cross-sectional, epidemiological study. Vitamin D data from 2208 patients from LAC PUC Goiás were analyzed for the prepandemic period (2016-2018) and pandemic (2020-2021), were divided into age groups and analyzed the relationship between hypovitaminosis and COVID-19 through the p-value of the Chi-square calculation in PAST version 4.03. The age group from 0 to 10 years (p= 0.058, 95% CI) was the only one that did not obtain a significant correlation and stated that the pandemic did not impact hypovitaminosis D in these patients. In the other age groups, from 11 to 20 years (p= 15.56. 10 -5, 95% CI%), from 21 to 60 years (p=: 4.84.10-20, CI 95%) and older than 60 years (p= 2.54. 10-9, 95% CI), confirmed the hypothesis that the covid-19 pandemic being related to hypovitaminosis D. The low levels of vitamin D are related to the COVID-19 pandemic in 3, of the 4 age groups investigated and, by bibliographic research, can define the course of the disease. Thus, supplementing the diet with vitamin D, under medical guidance, becomes a preventive and therapeutic measure in the case of COVID-19.